Association of the bitter taste receptor gene TAS2R38 (polymorphism RS713598) with sensory responsiveness, food preferences, biochemical parameters and body-composition markers. A cross-sectional study in Italy. (17th February 2018) - Perna, Simone; Riva, Antonella; Nicosanti, Giada; Carrai, Maura; Barale, Roberto; Vigo, Beatrice; Allegrini, Pietro; Rondanelli, Mariangela
Abstract: This study examined the relationship between TAS2R38 gene polymorphism (RS713598), G/G, C/G or C/C genotype, and sensory responsiveness, food preferences, biochemical parameters and body composition in a cross-sectional study in 118 adults (24 men and 94 women). The frequencies of C/C, G/G and C/G were respectively 20.3%, 29.7% and 50.0%. As regards taste responsiveness, subjects with G-allele had a higher perception threshold than the C/C genotype for 6-n-propyl-2-thiouracil (PROP) ( p < .05), and caffeine ( p < .05). The G-alleles had higher preferences for beer (OR: 6.25; p < .05), but lower for butter (OR: 0.64; p < .05) and cured meat (OR: 0.55; p < .05). Biochemical parameters and body composition markers did not differ between genotypes. Subjects with RS713598 polymorphism had a higher bitter taste perception threshold and higher or lower preferences for selected nutrient/energy dense foods, such as beer, butter and cured meat.